Molecular mechanisms of GABAB receptor activation: new insights from the mechanism of action of CGP7930, a positive allosteric modulator. (26th October 2004) - Binet, V.; Goudet, C.; Brajon, C.; Corre, L. Le; Acher, F.; Pin, J.-P.; Prézeau, L.
Abstract : The GABAB (γ-aminobutyric acid-B) receptor is composed of two subunits, GABAB1 and GABAB2 . Both subunits share structural homology with other class-III G-protein-coupled receptors. They contain two main domains, a heptahelical domain typical of all G-protein-coupled receptors and a large ECD (extracellular domain). It has not been demonstrated whether the association of these two subunits is always required for function. However, GABAB2 plays a major role in coupling with G-proteins, and GABAB1 has been shown to bind GABA. To date, only ligands interacting with GABAB1 -ECD have been identified. In the present study, we explored the mechanism of action of CGP7930, a compound described as a positive allosteric regulator of the GABAB receptor. We have shown that it can weakly activate the wild-type GABAB receptor, but also the GABAB2 expressed alone, thus being the first described agonist of GABAB2 . CGP7930 retains its weak agonist activity on a GABAB2 subunit deleted of its ECD. Thus the heptahelical domain of GABAB2 behaves similar to a rhodopsin-like receptor. These results open new strategies for studying the mechanism of activation of GABAB receptor and examine any possible role of GABAB2 .